Implementasi Asas Legalitas dalam Penegakan Hukum terhadap Tindak Pidana Radikalisme Digital yang Berimplikasi pada Terorisme - Usrinase, Yulius; Rusmana, I Putu Edi; Darma, I Made Wirya; Antari, Putu Eva Ditayani (Universitas Kapuas, 2025)
The development of information and communication technology creates new legal challenges, particularly in the spread of radical ideology through digital platforms. This article examines the application of the principle of legality in law enforcement against digital radicalism with implications for terrorism in Indonesia. Using normative legal research with legislative, conceptual, and analytical approaches, this research focuses on the Criminal Code, the Electronic Information and Transactions Law, and the Terrorism Law. The research findings reveal regulatory gaps, unclear legal provisions, and difficulties in distinguishing between protected expression and radical content, which hinder effective law enforcement. These gaps allow perpetrators to exploit the digital space and evade legal accountability. The research concludes that comprehensive legal reform, a progressive legal approach, and stronger international cooperation are needed to ensure that criminal law remains adaptive to technological developments while upholding legal certainty and human rights.